Design handbook : concepts, materials, styles. - Fiell, Charlotte, 1965-; Fiell, Peter, 1958- (Hong Kong : Taschen, 2006)
Knowledge is power: A to Z design definitions At last: a highly affordable, user-friendly handbook on design that covers all the major concepts, materials, and styles over the last 150 years with concise, easy-to-understand definitions. And as you'd expect from TASCHEN, it's packed cover to cover with outstanding images too. An absolutely indispensable book for all design fans! The editors: Charlotte J. and Peter M. Fiell run a design consultancy in London specializing in the sale, acquisition, study and promotion of design artifacts. They have lectured widely, curated a number of exhibitions, and written numerous articles and books on design and designers, including TASCHEN?S 1000 Lights, 1000 Chairs, Design of the 20th Century, Industrial Design A-Z, Designing the 21st Century, and Scandinavian Design.
Keywords: Ontwerpen